Financial management practices and life satisfaction: Mediating effect of financial satisfaction - Eli A. Atatsi; Edem M Azila-Gbettor; Harriet Akuma-Zanu; Christopher Mensah (Cogent Education, 2023)
AbstractThis study examined the mediation effect of financial satisfaction on financial management practices and life satisfaction relationship among secondary school teachers. A convenience sample of 263 respondents took part in the study via the completion of self-administered questionnaire. Descriptive statistics and Partial Least Squares based on Structural Equation Modeling (PLS-SEM) were used in examining respondents’ profile and the research model and its related hypotheses, respectively. Financial management practices significantly and positively affect financial satisfaction and life satisfaction. Also, a significant positive nexus existed between financial satisfaction and life satisfaction. Further, the study shows that financial satisfaction mediates the nexus between financial management practices and life satisfaction. Teachers as well as education workers at all levels can take a cue from this study on how best to ascertain financial satisfaction and life satisfaction through quality financial management practices. This study provides useful information for all education managers and stakeholders in promoting life satisfaction among teachers through the organization of financial education courses and counselling programs to build financial literacy skills. Similarly, the study indicates an urgent need to improve the financial management practices and competencies of teachers. This research broadens the literature on the application of the spillover theory in issues of financial management, financial satisfaction and life satisfaction.